Laparoscopic pyeloplasty practice patterns in Canada - Skinner, Thomas A.A.; Witherspoon, Luke; Dergham, Ali; Warren, Jeffrey E.; Watterson, James; Blew, Brian (Canadian Urological Association Journal, 2018)
Introduction: Ureteropelvic junction obstruction (UPJO) is a condition characterized by partial or complete obstruction of urine transport from the renal pelvis to the ureter and can present with intermittent flank pain, recurrent urinary tract infections, renal stones, or renal dysfunction. While historically, open pyeloplasty was the gold standard for surgical management, laparoscopic methods to repair UPJO have largely taken over as the preferred approach for adolescent and adult patients. Despite near universal adoption of laparoscopic pyeloplasty among Canadian urologists, it remains a technically complex procedure and considerable variability exists in the procedural steps performed. Methods: An online survey was distributed to all urologists registered with the Canadian Urological Association (CUA). Participants were asked to describe their training background, comfort level with laparoscopic pyeloplasty, positioning preferences, procedural steps, and stenting practices. Results: A total of 100 board-certified urologists completed our survey, with approximately half from a community setting and half with academic affiliations (56% and 43%, respectively). The vast majority (98%) reported preferring the Anderson-Hynes (dismembered) pyeloplasty technique. Other technical steps of the procedure were variable among respondents, with no discernable pattern. Those who felt most comfortable with the procedure tended to perform a larger volume of laparoscopic pyeloplasties annually or work at higher-volume institutions. Conclusions: Laparoscopic pyeloplasty remains a technically challenging procedure that many Canadian urologists are uncomfortable performing. With this publication, we hope to create discussion among urologists and to reveal procedural tips that may improve comfort in tackling these complex cases.